STATE EMBLEMS AS A REFLECTION OF THE COMMUNTST AND POSTCOMMUNIST TRANSFORMATIONS - Романюк, О.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The author investigates the processes of establishment of communist regimes and post-communist transformations on the basis of semiotic analysis. The object of this study is the state emblems. The basic trends in the emblems caused by changes in the political regime and the nature of the state are detected.